Factors associated with low prevalence of Fuchs' uveitis syndrome in Japan - Yoneda, Yu; Usui, Yoshihiko; Tanaka, Rie; Hase, Keitaro; Namba, Kenichi; Kamoi, Koju; Takase, Hiroshi; Takeuchi, Masaki; Matsumiya, Wataru; Kusuhara, Sentaro; Takeda, Atsunobu; Yawata, Nobuyo; et al. (Frontiers in Medicine, 2022)
Aim To investigate the causes of low prevalence of Fuchs' uveitis syndrome (FUS) in Japan. Methods Medical records of 160 patients diagnosed with FUS at 14 uveitis specialty facilities in Japan were reviewed retrospectively. Results In 160 FUS patients, mean follow-up period before referral to our uveitis facilities was 31.6 ± 50.9 months. The most common reason for referral was idiopathic uveitis (61.9%), followed by cataract (25.0%), high intraocular pressure (IOP) including glaucoma (16.3%), and FUS (14.4%). Unilateral involvement was 96.9%. The most frequent ocular finding of FUS was anterior inflammation (91.9%), followed by stellate-shaped keratic precipitates (88.1%), cataract/pseudophakia (88.1%), diffuse iris atrophy (84.4%), vitreous opacity (62.5%), heterochromia (53.1%) and high IOP including glaucoma (36.3%). As treatments of these ocular findings, cataract surgery was performed in 52.5%, glaucoma surgery in 10.6%, and vitrectomy in 13.8%. Mean logMAR VA was 0.28 ± 0.59 at the initial visit, and decreased significantly to 0.04 ± 0.32 at the last visit. Proportions of FUS patients with BCVA <0.1 and 0.1 to <0.5 decreased, while that of ≥0.5 increased at the last visit compared with the initial visit. Conclusions Ocular findings of FUS in Japanese FUS patients were consistent with the characteristic features. The low prevalence of FUS in Japan may be a result of being overlooked and misdiagnosed as mild idiopathic uveitis, cataract, and/or glaucoma.